1979
DOI: 10.1007/bf02081960
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical basis of radiodiagnosis of the adrenal gland

Abstract: Studies on 220 human adrenal glands were carried out microscopically, microangiographically and by direct dissection following preliminary filling of the vessels with injection masses. The position, size and shape of the adrenals, as well as their intrinsic and extrinsic arterial and venous vasculature were assessed. In the present work attention was directed mainly to the venous architecture. The understanding of venous pattern is of considerable importance to those who perform and evaluate adrenophlebography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The right and left adrenals typically have three tributary veins each, i.e., the superior, lateral, and inferior TVs in the right adrenal as well as the superior-median, superior-lateral, and lateral TVs in the left adrenal. Very few connections have been identified between these TVs 12 . Therefore, ssAVS enables the identification of a specific adrenal segment(s) not producing aldosterone autonomously within an affected adrenal, thereby allowing bilateral adrenal surgery to be performed on bilateral PA while sparing unaffected adrenal segment(s).…”
Section: Introductionmentioning
confidence: 99%
“…The right and left adrenals typically have three tributary veins each, i.e., the superior, lateral, and inferior TVs in the right adrenal as well as the superior-median, superior-lateral, and lateral TVs in the left adrenal. Very few connections have been identified between these TVs 12 . Therefore, ssAVS enables the identification of a specific adrenal segment(s) not producing aldosterone autonomously within an affected adrenal, thereby allowing bilateral adrenal surgery to be performed on bilateral PA while sparing unaffected adrenal segment(s).…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature reports that SSA can branch profusely, such that their number could range from 1 to 30 from one or more sources ( Table 3 ) [ 3 , 12 , 42 ]. In addition, the commonest branching pattern in most studies was reported as 4 to 8 arteries [ 3 , 4 , 12 , 43 - 45 ]. On dissecting the fetal specimens, few authors concluded after that the number of MSA ranges mostly between 1 to 3 [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most relevent findings Greeff et al [27] Dutta [5] Manso and DiDio [12] Bianchi and Ferrari [4] Toni et al [15] Meikos [43] Mazza [44] Levi [45] Research chronology till present day SSA was reported to be absent in few cases. AA and RA were most common origin of MSA and frequently absent bilaterally.…”
Section: Name Of Researchermentioning
confidence: 99%
“…In sAVS, high aldosterone levels from one APA may be observed in not one, but two, and rarely three segments 7 due to potential inter-tributary anastomoses. 32 c CT-detected nodule was negative for CYP11B2, and another smaller nodule was positive for CYP11B2.…”
Section: Discussionmentioning
confidence: 93%
“…This result may be due to contamination of APA blood in the non‐APA blood drainer. In sAVS, high aldosterone levels from one APA may be observed in not one, but two, and rarely three segments 7 due to potential inter‐tributary anastomoses 32 . This contamination is especially likely if the nodules are relatively close to each other.…”
Section: Discussionmentioning
confidence: 99%